SMU and National Library Board Agreement (Institutional Knowledge at Singapore Management University, 1999)
The National Library Board and Singapore Management University sign a memorandum of understanding on 3 September 1999. Under the terms of the agreement, NLB will plan and manage library and information services for the university. Seated, left to right, NLB Chairman Tan Chin Nam, NLB Chief Executive Christopher Chia, SMU President Janice Bellace, and SMU Chairman Ho Kwon Ping.